KOMUNIKASI PARIWISATA DINAS PARIWISATA PEMUDA DAN OLAHRAGA KABUPATEN TANAH DATAR DALAM MENGEMBANGKAN BRAND TANAH DATAR AUTHENTIC MINANGKABAU - Setiawan, M. Satria; Firdaus, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Tanah Datar Regency is one of the regencies in West Sumatra Province with the capital city of Batusangkar. Tanah Datar Regency is one of the developing areas and is known as Luhak Nan Tuo or the oldest area in the history of Minangkabau culture. Tanah Datar Regency is one of the main tourism sectors in West Sumatra Province because it has tours that have reached national and international scales such as the Basa Pagaruyung Palace and Pacu Jawi. In recent years, Tanah Datar Regency has echoed their tourism branding, namely Tanah Datar Authentic Minangkabau, which is one step in advancing tourism in the area. Therefore, the purpose of this study was to determine the process of tourism communication in developing the Brand Tanah Datar Authentic Minangkabau by the Department of Tourism, Youth and Sports, Tanah Datar Regency.This study uses qualitative research methods. Data collection techniques used in this study are interviews, observation, and documentation, with 7 research subjects. Technique of data analysis by reducing data, collecting data, presenting data, drawing conclusions and evaluating using data validity checking techniques, namely extension of participation and triangulation.The results of this study indicate in developing Brand Tanah Datar Authentic Minangkabau that the Source is the Tourism Sector, Departement Tourism, Youth and Sport of Tanah Datar Regency because it has the ability and credibility as well as the ability of the Brand Tanah Datar Authentic Minangkabau. The messages used are persuasive and interesting informative. Use of channels or media through social media, conventional media, online media and events. The received in this case are primary audience, secondary audience and tertiary audience.